On the Numerical Solution of Two Dimensional Schrodinger Equation - SUBAŞI, Murat; ARAZ, Seda İğret; GÜNGÖR, Hakkı (International Journal of Mathematical Research, 2017)
This paper includes a MAPLE® code giving numerical solution of two dimensional Schrödinger equation in a functional space. The Galerkin method has been used to get the approximate solution. The results have been examined with numerical examples.